Supervised exercise after minor stroke: an evaluation from the perspective of patients and healthcare professionals - Rikke Steen Krawcyk; Katrine Vollbrecht Amdi; Christina Kruuse; Thordis Thomsen (Journal of Rehabilitation Medicine)
Objective: Maintaining long-term physical activity after a stroke is challenging. “The Stroke School”, a standardized physical exercise programme, was developed and patients’ and healthcare professionals’ experiences of participating were explored.